C-TiO2 composite material taking carbon source as raw material as well as preparation method and application of C-TiO2 composite material
By using cheap carbon sources to prepare C-TiO2 composite materials, forming a tightly bound carbon layer, the problems of electrocatalytic inertia and high production costs in electrocatalytic water decomposition are solved, and efficient and stable application of electrocatalytic water decomposition is achieved. and high-value utilization of carbon sources.
Patent Information
- Application Number
- CN202411715847.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing titanium dioxide materials have electrocatalytic inertia in electrocatalytic water decomposition, and the high production cost limits its large-scale application in green hydrogen production.
C-TiO2 composite materials are prepared by cheap carbon sources. By recycling the negative electrode graphite of retired power lithium battery or using cheap organic matter as carbon source, a closely bound carbon layer with TiO2 powder during high-temperature calcination is prepared to prepare efficient and stable oxygen evolution Catalytic electrode.
It realizes efficient and stable ampere-level current density application, reduces the production cost of the electrolytic hydrogen production process, and provides a high-value utilization solution for cheap carbon sources.
Smart Images

Figure CN119406395A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a C-TiO2 composite material using a carbon source as a raw material, and a preparation method and application thereof. Background Art
[0002] Titanium dioxide has good chemical stability and electrochemical resistance, so it is widely used in various energy conversion and storage materials. However, the band gap of titanium dioxide is as high as 3.2eV, and its electrical conductivity is low, which leads to an increase in interface contact impedance, hindering the application of titanium dioxide in electrochemical devices. In order to improve the electrical conductivity of titanium dioxide materials, the composite of titanium dioxide and highly conductive carbon materials is one of the research directions. For example, invention patent CN201810191246X discloses a GO-TiO2 nanorod composite nanoparticle and a preparation method thereof, wherein GO particles (redox graphene) are prepared by a redox method, and TiO2 nanorods are grown on the surface of flaky GO by electrochemical and chemical bath deposition methods; invention patent CN2022108599970 discloses an oxygen-defective nanocarbon layer-coated titanium dioxide electrode, a preparation method thereof, and a magnesium battery, wherein the nanocarbon layer is formed by infiltrating the nanorods with a mixed solution of dopamine hydrochloride and tris(hydroxymethyl)aminomethane and then calcining and carbonizing. However, the prices of carbon sources such as dopamine hydrochloride and redox graphene are high, and the production cost of the composite material formed by titanium dioxide and carbon materials is high, which hinders the low-cost large-scale application of related processes.
[0003] Based on this, using cheap carbon sources to modify titanium dioxide materials will bring huge economic and social benefits.
[0004] In addition, titanium dioxide has an adjustable band structure and excellent light capture ability. As a promising photocatalyst, titanium dioxide material shows important application potential in photocatalytic water decomposition to produce hydrogen. However, photocatalytic hydrogen production is limited by unstable environmental factors and is difficult to carry out continuously and stably. Electricity-based electrocatalytic water decomposition to produce hydrogen is considered to be a very promising way to produce green hydrogen. However, titanium dioxide materials are electrocatalytically inert, and titanium dioxide suitable for photocatalytic hydrogen production is difficult to use in electrocatalytic water decomposition. Using titanium dioxide as a carrier to load a catalyst is one of the current research ideas for using titanium dioxide in electrolytic water decomposition to produce hydrogen. For example, invention patent CN2021105760082 discloses a loaded RuO x / F-TiO2 oxygen evolution catalyst, used for the kinetically slow oxygen evolution half-reaction in electrocatalytic water decomposition, in which TiO2 is used as an efficient carrier. Invention patent CN2021112724521 discloses a supported iridium catalyst, in which metallic iridium is supported on a titanium dioxide carrier, and is used to catalyze the anode oxygen evolution reaction in the process of water electrolysis.
[0005] It can be seen that in the prior art, titanium dioxide is generally used as a carrier of catalytically active substances to reduce the use of precious metal catalysts and reduce the cost of catalyst production. Despite this, the catalysts obtained in the above schemes are all powder catalysts, which have weak binding force with the conductive substrate. In industrial ampere-level electrocatalytic water decomposition, a large amount of gas bubbles will continuously impact the catalyst-conductive substrate interface of the electrode, causing the catalyst to fall off, thereby causing the electrode activity to decay. Looking at the existing titanium dioxide powder-type composite materials, none of them can achieve efficient and stable ampere-level electrocatalytic water decomposition applications, which greatly limits the large-scale promotion of titanium dioxide materials in electrochemical green hydrogen production.
[0006] In summary, if titanium dioxide-modified materials can be prepared with cheap carbon sources and new application methods are developed so that titanium dioxide-modified materials can be directly used in the electrocatalytic water decomposition hydrogen production process, the production cost of the water electrolysis hydrogen production process will be reduced. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a C-TiO2 composite material with a carbon source as a raw material, and a preparation method and application thereof. The preparation of the C-TiO2 composite material with a cheap carbon source as a raw material can effectively reduce the environmental pollution caused by retired new energy power lithium batteries, and at the same time provide a feasible solution for the high-value utilization of cheap carbon sources;
[0008] Another object of the present invention is to provide an application method of the C-TiO2 composite material prepared as above, propose a "chloride ion-assisted microbattery corrosion" strategy, apply the C-TiO2 composite material in the field of electrocatalytic water decomposition, and prepare an efficient and stable oxygen evolution catalytic electrode, which can realize ampere-level current density application for industrial needs.
[0009] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0010] In the first aspect of the present invention, the present invention provides a method for preparing a C-TiO2 composite material using a carbon source as a raw material, as follows:
[0011] A1. Dispersing the carbon source and TiO2 powder in a polar solvent to obtain a suspension A;
[0012] A2, heating the suspension A under stirring conditions to volatilize the ethanol aqueous solution to obtain a mixture B;
[0013] A3, calcining the mixture B to obtain a C-TiO2 composite material;
[0014] The carbon source includes one or both of a first carbon source and a second carbon source, the first carbon source is elemental carbon, and the second carbon source is an organic matter that can be cracked to generate carbon.
[0015] Preferably, the first carbon source includes recycled conductive carbon material, more preferably, the first carbon source includes negative electrode graphite recovered from retired power lithium batteries; the second carbon source includes one or more of urea, citric acid and glucose.
[0016] Preferably, in step A1, a chloride ion source is also added, and the polar solvent refers to a solvent that can dissolve the chloride ion source and organic matter, and the carbon source, TiO2 powder and the chloride ion source are dispersed in the polar solvent to form a suspension A, wherein the chloride ion source includes one or both of sodium chloride and potassium chloride;
[0017] In step A1, the mass ratio of the carbon source, TiO2 powder and chloride ion source is (0.2-10):1:(0-1).
[0018] More preferably, the polar solvent includes an ethanol aqueous solution, and the mass ratio of water to ethanol in the carbon source, TiO2 powder, chloride ion source and the ethanol aqueous solution is (0.2-10):1:(0-1):(2-10):(2-10), and more preferably, in the ethanol aqueous solution, the mass ratio of water to ethanol is 1:(0.5-4).
[0019] Preferably, in step A2, the heating treatment temperature is 50 to 80° C., and the heating time is 1 to 12 hours.
[0020] Preferably, in step A3, the calcination temperature is 80-600°C, the calcination time is 1-12h, and the calcination treatment is carried out in an oxygen-containing atmosphere or an inert atmosphere. Specifically, when the carbon source is the first carbon source, the calcination treatment is carried out in an oxygen-containing atmosphere or an inert atmosphere, and when the carbon source is the second carbon source, the calcination treatment is carried out in an inert atmosphere.
[0021] In a second aspect of the present invention, the present invention provides a C-TiO2 composite material, which is prepared by the above-mentioned preparation method, wherein the C-TiO2 composite material is formed by using carbon as a carrier and TiO2 primary particles are loaded on the carbon carrier. Preferably, the particle size range of the TiO2 primary particles is 5nm to 5μm, and the particle size range of the carbon carrier is 5 to 100μm.
[0022] In the third aspect of the present invention, the present invention proposes an application of a C-TiO2 composite material as follows:
[0023] B1, dispersing the prepared C-TiO2 composite material in a polar solvent to obtain slurry C;
[0024] B2, spraying slurry C onto the surface of the iron-nickel alloy, and obtaining an oxygen evolution electrode after drying;
[0025] B3, using the prepared oxygen evolution electrode in an electrochemical water splitting process;
[0026] Wherein, in step B1, when the C-TiO2 composite material does not contain a chloride ion source, step B1 further adds a chloride ion source dispersed in an ethanol aqueous solution; the polar solvent refers to a solvent that can dissolve the chloride ion source and organic matter.
[0027] Preferably, in step B1, the mass ratio of the C-TiO2 composite material to the chloride ion source is (1-10):(0-20).
[0028] Preferably, in step B1, the polar solvent includes an ethanol aqueous solution, the chloride ion source includes one or both of sodium chloride and potassium chloride, and the mass ratio of water and ethanol in the C-TiO2 composite material, the chloride ion source, and the ethanol aqueous solution is (1-10):(0-20):(40-400):(40-400), and more preferably, the mass ratio of water to ethanol is 1:(0.5-4).
[0029] Preferably, in step B2, the spraying amount of slurry C is calculated based on the mass ratio of the C-TiO2 composite material to the area ratio of the iron-nickel alloy, and is 0.1 to 2.0 mg / cm 2 .
[0030] Preferably, in step B2, the drying time is 0.2 to 12 hours.
[0031] Beneficial effects:
[0032] The present invention uses recycled or cheap carbon sources as raw materials, and cleverly utilizes the defect sites on the graphite surface recovered from the negative electrode of retired power lithium batteries to firmly anchor the titanium dioxide powder; or utilizes the cracking reaction of the cheap carbon source during high-temperature calcination to in-situ generate a carbon layer that is tightly combined with the titanium dioxide powder. The process scheme of the present invention realizes simple and efficient modification of titanium dioxide materials, has a short process flow, high reliability, and is easy to achieve large-scale production.
[0033] The present invention develops a new use of graphite recovered from the negative electrode of retired power lithium batteries, uses it as a carbon source to prepare C-TiO2 composite materials, and applies it to ampere-level electrochemical water decomposition for industrial needs. It can replace precious metals in traditional catalytic electrodes, has high economic value, and solves the problems of high pollution, low value, and difficult treatment of recycled graphite, and has obvious social benefits.
[0034] The present invention successfully applies C-TiO2 composite materials in the field of electrocatalytic water decomposition through the strategy of "chloride ion-assisted micro-battery corrosion", inducing the construction of micro-galvanic cells between C-TiO2 composite materials and the conductive substrate iron-nickel alloy, and further generating highly catalytically active substances that are tightly bonded to the substrate. The oxygen evolution catalytic electrode thus prepared can still maintain excellent activity and stability at high current density, and can achieve ampere-level current density applications for industrial needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope image of the negative electrode graphite recovered from the retired new energy power lithium battery in Example 1;
[0036] Figure 2 is a scanning electron microscope image of the nano-sized TiO2 powder in Example 1;
[0037] Figure 3 is a scanning electron microscope image of the C-TiO2 composite material in Example 1;
[0038] Figure 4 is the X-ray photoelectron spectrum of the C-TiO2 composite material in Example 1;
[0039] Figure 5 The electrochemical oxygen evolution reaction activity test curve of the high-efficiency oxygen evolution electrode prepared by induction of the C-TiO2 composite material in Example 1;
[0040] Figure 6 is a scanning electron microscope image of the C-TiO2 composite material in Example 2;
[0041] Figure 7 The electrochemical oxygen evolution reaction activity test curve of the high-efficiency oxygen evolution electrode prepared by induction of the C-TiO2 composite material in Example 2;
[0042] Figure 8 is a scanning electron microscope image of the C-TiO2 composite material in Example 3;
[0043] Fig. 9 The electrochemical oxygen evolution reaction activity test curve of the high-efficiency oxygen evolution electrode prepared by induction of the C-TiO2 composite material in Example 3;
[0044] Fig.10 is a scanning electron microscope image of the C-TiO2 composite material in Example 4;
[0045] Fig.11 The electrochemical oxygen evolution reaction activity test curve of the high-efficiency oxygen evolution electrode prepared by induction of the C-TiO2 composite material in Example 4;
[0046] Fig.12 The electrochemical oxygen evolution reaction activity test curve of the oxygen evolution electrode prepared from the C-TiO2 composite material in Comparative Example 1;
[0047] Fig.13 This is the electrochemical oxygen evolution reaction activity test curve of the oxygen evolution electrode prepared with TiO2 material in Comparative Example 2. DETAILED DESCRIPTION
[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.
[0049] The present invention proposes a C-TiO2 composite material with a carbon source as a raw material, carbon as a carrier, and TiO2 primary particles loaded on the carbon carrier, wherein the particle size range of the TiO2 primary particles is about 5nm to 5μm, the particle size range of the carbon carrier is about 5 to 100μm, and the source of the carbon carrier is a cheap or recycled carbon source, and the recycled carbon source includes recycled graphite, such as negative electrode graphite carbon recycled from retired power lithium batteries, and the cheap carbon source includes urea, citric acid, glucose and other low-priced carbon sources. In the case of using recycled carbon sources, the environmental pollution caused by retired new energy power lithium batteries can also be effectively reduced.
[0050] The present invention also proposes a method for preparing a C-TiO2 composite material using a carbon source as a raw material, the steps are as follows:
[0051] A1. Dispersing the carbon source and TiO2 powder in a polar solvent to obtain a suspension A;
[0052] A2, heating the suspension A under stirring conditions to volatilize the polar solvent to obtain a mixture B;
[0053] A3. Calcine the mixture B to obtain a C-TiO2 composite material.
[0054] In step A1, the carbon source includes a first carbon source and a second carbon source. The first carbon source is elemental carbon. The first carbon source includes recycled conductive carbon materials, such as recycled graphite. The recycled graphite can be negative electrode graphite recovered from retired new energy power lithium batteries. It is easy to understand that the recycled graphite can also be pure conductive carbon materials recovered from other fields, such as industrial production waste. The graphite electrodes used in the production process of steel mills, aluminum smelters, silicon plants, etc. will be worn out after a period of use and become waste graphite electrodes; the second carbon source is an organic matter that can be cracked to generate carbon, and cheap organic matter is preferably used as a cheap carbon source, such as urea, citric acid and glucose.
[0055] Long-term charge and discharge cycles cause the surface of the graphite recycled from the negative electrode of retired power lithium batteries to contain more defects, and these defects can serve as strong anchoring points for titanium dioxide. Therefore, after a three-step treatment process of dispersing and mixing the recycled graphite and titanium dioxide powder with a solvent, volatilizing the solvent under stirring and heating, and calcining at high temperature, a stable C-TiO2 composite material can be obtained.
[0056] Cheap carbon sources such as urea, citric acid, and glucose will crack under high temperature conditions. Therefore, mixing these carbon sources with titanium dioxide powder and calcining them at high temperature can in situ generate a carbon layer that is tightly bonded to titanium dioxide, thereby obtaining a stable C-TiO2 composite material.
[0057] In step A1, a chloride ion source is also added, and the carbon source, TiO2 powder and the chloride ion source are dispersed in a polar solvent to form a suspension A, wherein the chloride ion source includes one or both of sodium chloride and potassium chloride.
[0058] In step A1, the TiO2 powder is nano-sized TiO2 powder and / or micro-sized TiO2 powder.
[0059] In step A1, the polar solvent refers to a solvent that can dissolve the chloride ion source and the organic matter, and can be a mixed solvent or a pure substance. Preferably, the polar solvent is an ethanol aqueous solution. In addition, the polar solvent can also be water, an aqueous solution of a low molecular alcohol / ketone such as an ethylene glycol aqueous solution.
[0060] In step A1, the mass ratio of the carbon source, TiO2 powder and chloride ion source is (0.2-10):1:(0-1).
[0061] In step A1, when the polar solvent is an ethanol aqueous solution, the mass ratio of water to ethanol in the carbon source, TiO2 powder, chloride ion source and the ethanol aqueous solution is (0.2-10):1:(0-1):(2-10):(2-10).
[0062] In step A1, the mass ratio of water to ethanol in the ethanol aqueous solution may be 1:(0.5-4). The mass ratio of water to ethanol in the ethanol aqueous solution does not affect the preparation of the product, but does affect the drying speed.
[0063] In step A2, the heating treatment temperature is 50 to 80°C, and the heating time is 1 to 12 hours. The heating can be directly performed in an air atmosphere.
[0064] In step A3, the calcination temperature is 80-600° C., the calcination time is 1-12 hours, and the calcination treatment is carried out in an oxygen-containing atmosphere or an inert atmosphere, wherein the oxygen-containing atmosphere can be an air atmosphere, and the inert atmosphere can be a nitrogen atmosphere or an inert gas such as an argon atmosphere.
[0065] It is easy to understand that when the carbon source is elemental carbon, it is necessary to avoid burning of the carbon source during calcination, so it is necessary to select a temperature lower than the ignition point of elemental carbon or to select calcination in an oxygen-free inert environment. For example, when the ignition point of elemental carbon is higher than 600°C (such as graphite), the calcination temperature range and calcination atmosphere of the present invention can be used. When the ignition point of elemental carbon is between 800 and 600°C, a temperature lower than the ignition point of the elemental carbon can be selected for calcination, or an inert atmosphere can be selected and a higher calcination temperature can be used for calcination. When the carbon source is an organic matter, calcination requires cracking and carbonizing of the organic matter, the calcination temperature is greater than or equal to the temperature of cracking and carbonizing of the organic matter, and calcination is performed in an inert atmosphere to avoid oxidation of the organic matter.
[0066] The typical morphology of the C-TiO2 composite material prepared by the preparation method of the present invention is TiO2 particles loaded on a bulk carbon carrier.
[0067] The C-TiO2 composite material prepared by the present invention can be used in the field of energy conversion and storage, for example, it can be used in the field of electrochemical water decomposition. The specific application methods are as follows:
[0068] B1, dispersing the prepared C-TiO2 composite material and a chloride ion source in a polar solvent to obtain slurry C;
[0069] B2, spraying slurry C onto the surface of the iron-nickel alloy, and obtaining an oxygen evolution electrode after drying;
[0070] B3. Use the prepared oxygen evolution electrode in the electrochemical water splitting process.
[0071] In step B1, the chloride ion source includes one or both of sodium chloride and potassium chloride. The presence of chloride ions in the slurry C, which are precipitated in situ from the C-TiO2 composite material or added exogenously, can destroy the passivation film on the surface of the iron-nickel alloy, which is conducive to the attachment of the C-TiO2 composite material to the surface of the iron-nickel alloy.
[0072] In step B1, the polar solvent refers to a solvent that can dissolve the chloride ion source and the organic matter, and can be a mixed solvent or a pure substance. Preferably, the polar solvent is an ethanol aqueous solution. In addition, the polar solvent can also be water, an aqueous solution of a low molecular alcohol / ketone such as an ethylene glycol aqueous solution.
[0073] In step B1, the mass ratio of the C-TiO2 composite material to the chloride ion source is (1-10):(0-20).
[0074] In step B1, the polar solvent is an ethanol aqueous solution, and the mass ratio of water and ethanol in the C-TiO2 composite material, the chloride ion source and the ethanol aqueous solution is (1-10):(0-20):(40-400):(40-400). Preferably, the mass ratio of water to ethanol can be 1:(0.5-4). The mass ratio of water to ethanol in the ethanol aqueous solution does not affect the preparation of the product, but affects the drying speed.
[0075] In step B2, the main components of the iron-nickel alloy are iron and nickel, wherein the mass fraction of the iron element is 50-80%, and the mass fraction of the nickel element is 20-50%. In the present invention, the iron-nickel alloy refers to an alloy material whose main elements are iron and nickel, and other metal elements may also be added.
[0076] In step B2, the spraying amount of slurry C is calculated based on the mass ratio of the C-TiO2 composite material to the area ratio of the iron-nickel alloy, and is 0.1-2.0 mg / cm 2 , that is, the spray slurry contains 0.1 to 2.0 mg of C-TiO2 composite material per square centimeter of the iron-nickel alloy surface.
[0077] In step B2, the drying time is 0.2 to 12 hours, and the drying can be carried out in an air atmosphere.
[0078] It should be noted that in the present invention, if a chloride ion source is added in the preparation step, then the chloride ion source may not be added in the application step. Conversely, if the chloride ion source is not added in the preparation step, then the chloride ion source needs to be added in the application step.
[0079] The C-TiO2 composite material prepared by the present invention can be used to prepare a high-efficiency oxygen evolution electrode, and its principle is as follows: firstly, the presence of chloride ions in the slurry C, which are in-situ precipitated from the C-TiO2 composite material or added exogenously, will destroy the passivation film on the surface of the conductive substrate iron-nickel alloy and reduce the corrosion resistance of the iron-nickel alloy; secondly, thanks to the enhanced conductivity of the C-TiO2 composite material and the potential difference between the C-TiO2 composite material and the surface of the iron-nickel alloy, the C-TiO2 composite material forms a large number of micro primary cells on the surface of the iron-nickel alloy; at this time, the iron-nickel alloy serves as the negative electrode of the micro primary cell, and iron-nickel ions are continuously precipitated, and the C-TiO2 composite material serves as the positive electrode of the micro primary cell, and an oxygen reduction reaction occurs to generate hydroxide; thus, at the solid-solid interface and the surrounding area between the C-TiO2 composite material and the iron-nickel alloy, the precipitated iron-nickel ions are combined with hydroxide to obtain a high-activity iron-nickel hydroxide tightly combined with the conductive substrate as a catalytic active phase for oxygen evolution reaction, which can be applied in realizing ampere-level current density for industrialization needs.
[0080] The technical solution of the present invention is described in detail below with specific embodiments.
[0081] Example 1
[0082] A1. Disperse 2 parts of negative electrode graphite recycled from retired new energy power lithium batteries, 6 parts of nano-TiO2 powder, and 3 parts of potassium chloride in 30 parts of water and 36 parts of anhydrous ethanol by weight to obtain suspension A.
[0083] A2. Under stirring, the suspension A is heated to obtain a mixture B, wherein the heating temperature is 70° C., the heating time is 5 h, and the heating environment is an air environment;
[0084] A3. Calcinate the mixture B to obtain a C-TiO2 composite material, wherein the calcination temperature is 100°C, the calcination time is 8 hours, and the calcination environment is an air environment.
[0085] B1. Dispersing 3 parts of C-TiO2 composite material and 1 part of potassium chloride in a mixed solution of 250 parts of water and 250 parts of ethanol by weight to obtain slurry C;
[0086] B2. According to the mass ratio of C-TiO2 composite material to the area of iron-nickel alloy, slurry C is sprayed onto the surface of iron-nickel alloy (the mass fraction of iron in the alloy is about 40%, and the mass fraction of nickel is about 60%), with a spraying amount of 0.4 mg / cm 2 ;
[0087] The iron-nickel alloy sprayed with slurry C was placed in air for 2 hours to dry, thereby obtaining a high-efficiency oxygen evolution electrode.
[0088] like Figure 1 As shown, it is a scanning electron microscope image of the recycled negative electrode graphite of retired new energy power lithium batteries. The recycled negative electrode graphite presents a block structure of micrometer scale (10 to 50 μm).
[0089] like Figure 2 As shown in FIG. 1 , it is a scanning electron microscope image of nano-scale TiO2 powder. There are a large number of nano-scale primary particles in the nano-scale TiO2 powder, and the primary particles are agglomerated into micron-scale (0.5-3 μm) secondary particles. In this embodiment, negative electrode graphite recovered from power lithium batteries is used as a carbon source, and the nano-scale TiO2 powder is modified according to the above steps.
[0090] like Figure 3 The figure shows a scanning electron microscope image of the obtained C-TiO2 composite material. The surface of the blocky recycled negative electrode graphite is loaded with a large amount of nano-TiO2 powder. The introduction of highly conductive recycled negative electrode graphite can effectively improve the conductivity of nano-TiO2 materials and promote their application in electrochemical devices.
[0091] like Figure 4As shown, it is the X-ray photoelectron spectrum of C-TiO2 composite material. The detection of K and Cl elements indicates that the potassium chloride introduced in the preparation process is successfully retained in the C-TiO2 composite material. In the process of preparing efficient oxygen evolution electrode induced by C-TiO2 composite material, the presence of chloride ions in situ precipitated from C-TiO2 composite material or added exogenously in the slurry can destroy the passivation film on the surface of the conductive substrate iron-nickel alloy and reduce the corrosion resistance of the iron-nickel alloy. At the same time, thanks to the enhanced conductivity of C-TiO2 composite material and its potential difference with the surface of iron-nickel alloy, C-TiO2 composite material forms a large number of micro-galvanic cells on the surface of iron-nickel alloy; at this time, iron-nickel alloy acts as the negative electrode of micro-galvanic cell, iron-nickel ions are continuously precipitated, and C-TiO2 composite material acts as the positive electrode of micro-galvanic cell, oxygen reduction reaction occurs to generate hydroxide; thus, at the solid-solid interface and surrounding of C-TiO2 composite material and iron-nickel alloy, the precipitated iron-nickel ions combine with hydroxide to obtain a highly active iron-nickel hydroxide tightly combined with the conductive substrate as the catalytic active phase of oxygen evolution reaction.
[0092] A three-electrode test system was used, with the high-efficiency oxygen evolution electrode prepared by induction of the C-TiO2 composite material in this embodiment as the working electrode, the platinum sheet as the counter electrode, the mercuric oxide as the reference electrode, and 1 mol / L potassium hydroxide as the electrolyte. A GamryInterface 1000 electrochemical workstation was used to perform a linear sweep voltammetric curve test to characterize the oxygen evolution reaction activity of the working electrode. The specific test parameters are as follows: the scan rate is 5mv / S, and the scan voltage range is 1.2-1.65V (vs.RHE, relative to the reversible hydrogen electrode). The test results are as follows: Figure 5 As shown in Figure 2, the electrocatalytic activity of the Fe-Ni alloy with C-TiO2 composite material on the surface was significantly improved. When the current density reached 100 mA / cm 2 When the overpotential is 352 mV, the high-efficiency oxygen evolution electrode prepared by induction of the C-TiO2 composite material in this embodiment can also generate an ampere-level current density (1000 mA / cm 2 ).
[0093] Example 2
[0094] A1. By weight, 3 parts of negative electrode graphite recycled from retired new energy power lithium batteries, 5 parts of micron-sized TiO2 powder, and 0 parts of sodium chloride are dispersed in 30 parts of water and 40 parts of anhydrous ethanol to obtain a suspension A.
[0095] A2. Under stirring, the suspension A is heated to obtain a mixture B, wherein the heating temperature is 60° C., the heating time is 10 h, and the heating environment is an air environment;
[0096] A3, calcining the mixture B to obtain a C-TiO2 composite material, wherein the calcination temperature is 400°C, the calcination time is 1 hour, and the calcination environment is an air environment;
[0097] B1. Dispersing 3 parts of C-TiO2 composite material and 4 parts of sodium chloride in a mixed solution of 230 parts of water and 280 parts of ethanol by weight to obtain slurry C;
[0098] B2. According to the mass ratio of C-TiO2 composite material to the area ratio of iron-nickel alloy, slurry C is sprayed onto the surface of iron-nickel alloy (the mass fraction of iron in the alloy is about 40%, and the mass fraction of nickel is about 60%), with a spraying amount of 0.6 mg / cm 2 ;
[0099] The iron-nickel alloy sprayed with slurry C was placed in air for 6 hours to dry, thereby obtaining a high-efficiency oxygen evolution electrode.
[0100] like Figure 6 As shown in FIG. 1 , a scanning electron microscope image of a C-TiO2 composite material obtained by using the recycled negative electrode graphite from retired new energy power lithium batteries as a carbon source in this embodiment, a large amount of TiO2 powder is loaded on the surface of the blocky recycled negative electrode graphite. The introduction of highly conductive recycled negative electrode graphite can effectively improve the conductivity of TiO2 materials and promote their application in electrochemical devices.
[0101] The process of preparing the high-efficiency oxygen evolution electrode induced by the C-TiO2 composite material and the reaction activity test in this embodiment are similar to those in Example 1. Figure 7 As shown in Figure 2, the electrocatalytic activity of the Fe-Ni alloy with C-TiO2 composite material on the surface was significantly improved. When the current density reached 100 mA / cm 2 When the overpotential is 362 mV, the high-efficiency oxygen evolution electrode prepared by induction of the C-TiO2 composite material in this embodiment can also generate an ampere-level current density (1000 mA / cm 2 ).
[0102] Example 3
[0103] A1. Disperse 15 parts of urea, 6 parts of nano-TiO2 powder and 3 parts of potassium chloride in 35 parts of water and 40 parts of anhydrous ethanol to obtain suspension A.
[0104] A2. Under stirring, the suspension A is heated to obtain a mixture B, wherein the heating temperature is 65° C., the heating time is 12 h, and the heating environment is an air environment;
[0105] A3, calcining the mixture B to obtain a C-TiO2 composite material, wherein the calcination temperature is 500°C, the calcination time is 3h, and the calcination environment is a nitrogen atmosphere;
[0106] B1. Dispersing 1 part of C-TiO2 composite material and 0 part of potassium chloride in a mixed solution of 50 parts of water and 50 parts of ethanol by weight to obtain slurry C;
[0107] B2. According to the mass ratio of C-TiO2 composite material to the area of iron-nickel alloy, slurry C is sprayed onto the surface of iron-nickel alloy (the mass fraction of iron in the alloy is about 40%, and the mass fraction of nickel is about 60%), with a spraying amount of 0.8 mg / cm 2 ;
[0108] The iron-nickel alloy sprayed with slurry C was placed in air for 8 hours to dry, thereby obtaining a high-efficiency oxygen evolution electrode.
[0109] like Figure 8 As shown in FIG. 1 , it is a scanning electron microscope image of the C-TiO2 composite material obtained by using urea as the carbon source in this embodiment. The surface of the blocky urea pyrolytic carbon is loaded with a large amount of TiO2 powder. The introduction of highly conductive urea pyrolytic carbon can effectively improve the conductivity of TiO2 materials and promote their application in electrochemical devices.
[0110] The process of preparing the high-efficiency oxygen evolution electrode induced by the C-TiO2 composite material and the reaction activity test in this embodiment are similar to those in Example 1. Fig. 9 As shown in Figure 2, the electrocatalytic activity of the Fe-Ni alloy with C-TiO2 composite material on the surface was significantly improved. When the current density reached 100 mA / cm 2 When the overpotential is 349 mV, the high-efficiency oxygen evolution electrode prepared by induction of the C-TiO2 composite material in this embodiment can also generate an ampere-level current density (1000 mA / cm 2 ).
[0111] Example 4
[0112] A1. Disperse 16 parts of citric acid, 5 parts of micron-sized TiO2 powder, and 1 part of sodium chloride in 30 parts of water and 35 parts of anhydrous ethanol to obtain suspension A.
[0113] A2. Under stirring, the suspension A is heated to obtain a mixture B, wherein the heating temperature is 80° C., the heating time is 4 h, and the heating environment is an air environment;
[0114] A3, calcining the mixture B to obtain a C-TiO2 composite material, wherein the calcination temperature is 600°C, the calcination time is 2h, and the calcination environment is an argon atmosphere;
[0115] B1. Dispersing 3 parts of C-TiO2 composite material and 2 parts of sodium chloride in a mixed solution of 250 parts of water and 250 parts of ethanol by weight to obtain slurry C;
[0116] B2. According to the mass ratio of C-TiO2 composite material to the area of iron-nickel alloy, slurry C is sprayed onto the surface of iron-nickel alloy (the mass fraction of iron in the alloy is about 40%, and the mass fraction of nickel is about 60%), with a spraying amount of 1.2 mg / cm 2 ;
[0117] The iron-nickel alloy sprayed with slurry C was placed in air for 12 hours to dry, thereby obtaining a high-efficiency oxygen evolution electrode.
[0118] like Fig.10 As shown in FIG. 1 , a scanning electron microscope image of the C-TiO2 composite material obtained by using citric acid as the carbon source in this embodiment is shown. The surface of the blocky citric acid pyrolytic carbon is loaded with a large amount of TiO2 powder. The introduction of highly conductive citric acid pyrolytic carbon can effectively improve the conductivity of TiO2 materials and promote their application in electrochemical devices.
[0119] The process of preparing the high-efficiency oxygen evolution electrode induced by the C-TiO2 composite material and the reaction activity test in this embodiment are similar to those in Example 1. Fig.11 As shown in Figure 2, the electrocatalytic activity of the Fe-Ni alloy with C-TiO2 composite material on the surface was significantly improved. When the current density reached 100 mA / cm 2 When the overpotential is 378 mV, the high-efficiency oxygen evolution electrode prepared by induction of the C-TiO2 composite material in this embodiment can also generate an ampere-level current density (1000 mA / cm 2 ).
[0120] Comparative Example 1
[0121] A1. Disperse 2 parts of negative electrode graphite recycled from retired new energy power lithium batteries, 6 parts of nano-TiO2 powder, and 3 parts of potassium chloride in 30 parts of water and 36 parts of anhydrous ethanol by weight to obtain suspension A.
[0122] A2. Under stirring, the suspension A is heated to obtain a mixture B, wherein the heating temperature is 70° C., the heating time is 5 h, and the heating environment is an atmospheric environment;
[0123] A3, calcining the mixture B to obtain a C-TiO2 composite material, wherein the calcination temperature is 100°C, the calcination time is 8 hours, and the calcination environment is an air environment;
[0124] B1. Dispersing 3 parts of C-TiO2 composite material and 1 part of potassium chloride in a mixed solution of 250 parts of water and 250 parts of ethanol by weight to obtain a suspension C;
[0125] B2. According to the mass ratio of C-TiO2 composite material to carbon cloth area, spray suspension C onto the surface of carbon cloth with a spraying amount of 0.4 mg / cm 2 ;
[0126] The carbon cloth sprayed with the suspension C was placed in the air for 2 hours to dry, thereby obtaining an oxygen evolution electrode.
[0127] The preparation method of the C-TiO2 composite material in this comparative example is consistent with that in Example 1. In the step of inducing the preparation of the oxygen evolution electrode with the C-TiO2 composite material, the iron-nickel alloy is replaced by carbon cloth.
[0128] A three-electrode test system was used, with the oxygen evolution electrode prepared by induction of the C-TiO2 composite material in this comparative example as the working electrode, the platinum sheet as the counter electrode, mercuric oxide as the reference electrode, and 1 mol / L potassium hydroxide as the electrolyte. A linear sweep voltammetric curve test was performed using a Gamry Interface 1000 electrochemical workstation to characterize the oxygen evolution reaction activity of the working electrode. The specific test parameters are as follows: the scan rate is 5mv / S, and the scan voltage range is 1.2-1.65V (vs. RHE, relative to the reversible hydrogen electrode). The test results are as follows: Fig.12 As shown, the carbon cloth with C-TiO2 composite material on the surface still has no obvious current response of oxygen evolution reaction even under high voltage. Compared with the results of Example 1, it is shown that the key to the application method of C-TiO2 composite material in the field of electrochemical water decomposition is to load it on the surface of iron-nickel alloy, and use the micro-galvanic cell formed by the solid-solid interface potential difference between the two to obtain a highly active iron-nickel hydroxide tightly combined with the conductive substrate as the catalytic active phase of oxygen evolution reaction.
[0129] Comparative Example 2
[0130] A1. Disperse 6 parts of nano-TiO2 powder and 3 parts of potassium chloride in 30 parts of water and 36 parts of anhydrous ethanol by weight to obtain suspension A.
[0131] A2. Under stirring, the suspension A is heated to obtain a mixture B, wherein the heating temperature is 70° C., the heating time is 5 h, and the heating environment is an air environment;
[0132] A3, calcining the mixture B to obtain a TiO2 material, wherein the calcination temperature is 100°C, the calcination time is 8 hours, and the calcination environment is an air environment;
[0133] B1. Disperse 3 parts of TiO2 material and 1 part of potassium chloride in a mixed solution of 250 parts of water and 250 parts of ethanol by weight to obtain a suspension C;
[0134] B2. According to the mass ratio of TiO2 material to the area of iron-nickel alloy, spray suspension C onto the surface of iron-nickel alloy (the mass fraction of iron in the alloy is about 40%, and the mass fraction of nickel is about 60%), with a spraying amount of 0.4 mg / cm 2 ;
[0135] The iron-nickel alloy sprayed with the suspension C was placed in air for 2 hours to dry, thereby obtaining an oxygen evolution electrode.
[0136] The preparation method of the TiO2 material in this comparative example is similar to that in Example 1, but no negative electrode graphite recycled from retired new energy power lithium batteries is added as a carbon source. The application method of the TiO2 composite material in this comparative example is consistent with that in Example 1.
[0137] A three-electrode test system was used, with the oxygen evolution electrode prepared by induction of TiO2 material in this comparative example as the working electrode, platinum sheet as the counter electrode, mercuric oxide as the reference electrode, and 1 mol / L potassium hydroxide as the electrolyte. A Gamry Interface 1000 electrochemical workstation was used to perform a linear sweep voltammetric curve test to characterize the oxygen evolution reaction activity of the working electrode. The specific test parameters are as follows: the scan rate is 5mv / S, and the scan voltage range is 1.2-1.65V (vs. RHE, relative to the reversible hydrogen electrode). The test results are as follows: Fig.13 As shown in the figure, the electrocatalytic activity of the iron-nickel alloy with TiO2 on the surface is limited. When the current density reaches 100mA / cm 2 The overpotential is 349mV, which is only slightly better than the 363mV of the iron-nickel alloy, and it is difficult to meet the ampere-level current density application requirements of industrialization. Compared with the results of Example 1, the importance of recycling negative electrode graphite carbon from retired new energy power lithium batteries is proved. Due to its low electrical conductivity, the unmodified TiO2 hinders the formation of a solid-solid interface micro-galvanic cell between it and the iron-nickel alloy, resulting in limited improvement in the catalytic activity of the obtained oxygen evolution electrode.
[0138] The embodiments provided by the present invention are described in detail above. Specific examples are used herein to describe the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the core idea of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a C-TiO2 composite material using a carbon source as a raw material, characterized in that: as follows: A1. Dispersing the carbon source and TiO2 powder in a polar solvent to obtain a suspension A; A2, heating the suspension A under stirring conditions to volatilize the polar solvent to obtain a mixture B; A3, calcining the mixture B to obtain a C-TiO2 composite material; The carbon source includes one or both of a first carbon source and a second carbon source, the first carbon source is elemental carbon, and the second carbon source is an organic matter that can be cracked to generate carbon.
2. The preparation method according to claim 1, characterized in that: In step A1, a chloride ion source is also added, and the polar solvent refers to a solvent that can dissolve the chloride ion source and organic matter, and the carbon source, TiO2 powder and the chloride ion source are dispersed in the polar solvent to form a suspension A, wherein the chloride ion source includes one or both of sodium chloride and potassium chloride; In step A1, the mass ratio of the carbon source, TiO2 powder and chloride ion source is (0.2-10):1:(0-1).
3. The preparation method according to claim 2, characterized in that: The polar solvent includes an ethanol aqueous solution, and the mass ratio of water to ethanol in the carbon source, TiO2 powder, chloride ion source and the ethanol aqueous solution is (0.2-10):1:(0-1):(2-10):(2-10).
4. The preparation method according to claim 2 or 3, characterized in that: The first carbon source includes recycled conductive carbon material. More preferably, the first carbon source includes negative electrode graphite recovered from retired power lithium batteries; the second carbon source includes one or more of urea, citric acid and glucose.
5. The preparation method according to claim 2 or 3, characterized in that: In step A2, the temperature of the heating treatment is 50 to 80°C; In step A3, the calcination temperature is 80-600° C. When the carbon source is the first carbon source, the calcination treatment is performed in an oxygen-containing atmosphere or an inert atmosphere. When the carbon source is the second carbon source, the calcination treatment is performed in an inert atmosphere.
6. A C-TiO2 composite material, characterized in that: The C-TiO2 composite material is prepared by the preparation method described in any one of claims 2 to 5, wherein carbon is used as a carrier and TiO2 particles are loaded on the carbon carrier.
7. An application of a C-TiO2 composite material, characterized in that: as follows: B1. Dispersing the C-TiO2 composite material obtained by the preparation method according to any one of claims 2 to 5 in a polar solvent to obtain slurry C; B2, spraying slurry C onto the surface of the iron-nickel alloy, and obtaining an oxygen evolution electrode after drying; B3, using the prepared oxygen evolution electrode in an electrochemical water splitting process; Wherein, in step B1, when the C-TiO2 composite material does not contain a chloride ion source, step B1 further adds a chloride ion source dispersed in a polar solvent.
8. The use according to claim 7, characterized in that: In step B1, the chloride ion source includes one or both of sodium chloride and potassium chloride, and the mass ratio of the C-TiO2 composite material to the chloride ion source is (1-10):(0-20).
9. The use according to claim 8, characterized in that: In step B1, the polar solvent includes an ethanol aqueous solution, and the mass ratio of the C-TiO2 composite material, the chloride ion source, and the water and ethanol in the ethanol aqueous solution is (1-10):(0-20):(40-400):(40-400).
10. The use according to any one of claims 7 to 9, characterized in that: In step B2, the spraying amount of slurry C is calculated based on the mass ratio of the C-TiO2 composite material to the area ratio of the iron-nickel alloy, and is 0.1-2.0 mg / cm 2 .
Citation Information
Patent Citations
Method for in-situ preparation of Fe / TiC composite powder by vacuum carbon thermal reduction
CN108080648A
Carbon-coupled ferronickel double-metal hydroxide and in-situ rapid preparation method and application thereof
CN116855998A
Method for manufacturing the nanoporous skeletonC material
US20060251565A1